Data Set for the Reporting of Carcinoma of the Renal Pelvis and Ureter—Nephroureterectomy and Ureterectomy Specimens: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (October 2019) - Samaratunga, Hemamali; Judge, Meagan; Delahunt, Brett; Srigley, John; Brimo, Fadi; Comperat, Eva; Koch, Michael; Lopez-Beltran, Antonio; Reuter, Victor; Shanks, Jonathan; Tsuzuki, Toyonori; van der Kwast, Theodorus; et al.
Abstract : Cancer reporting guidelines have been developed and utilized in many countries throughout the world. The International Collaboration on Cancer Reporting (ICCR), through an alliance of colleges and other pathology organizations in Australasia, United Kingdom, Ireland, Europe, USA, and Canada, has developed comprehensive standardized data sets to provide for global usage and promote uniformity in cancer reporting. Structured reporting facilitates provision of all necessary information, which ensures accurate and comprehensive data collection, with the ultimate aim of improving cancer diagnostics and treatment. The data set for primary carcinoma of the renal pelvis and ureter treated with nephroureterectomy or ureterectomy had input from an expert panel of international uropathologists. This data set was based on current evidence-based practice and incorporated information from the 2016 fourth edition of the World Health Organization (WHO) Bluebook on tumors of the urinary and male genital systems and the 2017 American Joint Committee on Cancer (AJCC) TNM staging eighth edition. This protocol applies to both noninvasive and invasive carcinomas in these locations. Reporting elements are considered to be essential ( required ) or nonessential ( recommended ). Required elements include operative procedure, specimens submitted, tumor location, focality and size, histologic tumor type, subtype/variant of urothelial carcinoma, WHO grade, extent of invasion, presence or absence of vascular invasion, status of the resection margins and lymph nodes and pathologic stage. The data set provides a detailed template for the collection of data and it is anticipated that this will facilitate appropriate patient management with the potential to foster collaborative research internationally.